Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper on Spain focuses on differences in regional productivity. Recent studies of income convergence among Spanish regions suggest that the convergence has been slow since 1980 reflecting persistent regional disparities in total factor productivity. The empirical analysis-employing stochastic frontier models-finds that, among other factors, differences in regions' skills mismatch and technology absorption capacity could be behind the disparities. A benchmarking exercise demonstrates significant potential growth benefits from policy measures that would bring regions closer to the frontier. Regional income disparities-driven by differences in total factor productivity (TFP) and unemployment-while not large compared with European peers, have been persistent in recent years. The economy's overall productivity frontier moved inward overtime, but this trend has slowed down after the crisis. The inward shift of the production frontier could be one of the explanations for the negative TFP growth observed before the crisis. Active labor market policies at the regional level could also work toward addressing skills mismatch and education outcomes.